Association between uric acid to high-density lipoprotein cholesterol ratio and moderate-to-severe perivascular spaces burden: a retrospective cross-sectional study - Lin, Jie; Zhuang, Jieying; Luo, Qian; Xiao, Ruiyan; Wang, Huijuan; Yang, Xudong; Cai, Jiangping (Frontiers in Neurology, 2025)
BackgroundPerivascular spaces (PVS) are critical for waste clearance in the central nervous system and are implicated in various neurological disorders. The uric acid to high-density lipoprotein cholesterol ratio (UHR) is a novel inflammatory-metabolic marker, but its association with PVS burden remains unexplored. This study investigated the association between UHR and moderate-to-severe PVS burden.MethodsA retrospective cross-sectional analysis was conducted on 808 patients between 2022 and 2024. UHR levels were calculated and categorized into quartiles. PVS burdens in the basal ganglia and centrum semiovale regions were assessed. Logistic regression, correlation, subgroup, and restricted cubic splines analyses were performed to evaluate the relationship between UHR and PVS burden. The net reclassification index (NRI) and integrated discrimination improvement (IDI) were calculated. Additionally, sensitivity analyses were performed to validate the robustness of the findings.ResultsUHR was significantly higher in patients with moderate-to-severe PVS burden compared to those with none-to-mild PVS burden (p < 0.001). Multivariate logistic regression revealed a positive, dose-dependent relationship between UHR and moderate-to-severe PVS burden (OR = 1.07, 95% CI: 1.03–1.12, p < 0.001). This association was consistent across the basal ganglia and centrum semiovale regions. Subgroup analyses suggested a consistent association across various subgroups, with LDL-C levels affecting the UHR-PVS relationship. Incorporating UHR into predictive models significantly improved the identification of moderate-to-severe PVS burden (NRI = 0.310, IDI = 0.013, p < 0.001).ConclusionOur findings indicate a significant association between UHR levels and moderate-to-severe PVS burden, demonstrating potential implications for PVS risk assessment and management.